FACTORS RELATED TO SCHOOL’S PREPAREDNESS IN FACING EARTHQUAKE DISASTERS IN DENPASAR CITY - Yustina Ni Putu Yusniawati; Putu Inge Ruth Suantika (Nurse and Health: Jurnal Keperawatan, 2020)
AbstractBackground: Earthquake is unpredictable, making it impertinent for all components of society to be prepared to handle, especially elementary school children. During earthquakes, students often experience panic, endangering their lives. It is, therefore, crucial to identify the factors affecting students' preparedness for disasters (LIPI, 2006).Objectives: This study aimed to determine the factors related to the preparedness of students in disaster prepared schools (DPS) to reduce earthquake risks in Denpasar City, Bali.Methods: This study used a descriptive correlative analytic design with a cross-sectional approach. The sample in this study were all students of Public Elementary Schools (PES) and private schools (PS) in grades 5 and 6 whose institutions have implemented DPS, and the location of the school is in the city of Denpasar. Students chosen as the research samples received a brief explanation of the research process on the first page of the electronic questionnaire and parents can give consent to be research respondents when they approve their child to be a research sample. The instruments used in this study were 50, where this questionnaire was a standard questionnaire modified by researchers from LIPI (2006), Amri et al.,(2017), Hirano et al., (2011), and Davis & Izadkhah (2008). The univariate analysis identifies each research variable, namely disaster preparedness factors (knowledge, attitudes, infrastructure and CIE) and student preparedness in DPS. The bivariate analysis used is the Gamma test when it meets the requirements. Multivariate analysis in this study used the logistic regression analysis.Results: The results of this study show that Communication, Information and Education (CIE) has a robust correlation with earthquake preparedness (r = 0.761 and p-value = 0.000). CIE of DPS schools that are not good enough will lead to low preparedness of DPS students in earthquake disaster management by nine times.Conclusion: Knowledge, attitudes, infrastructure and CIE have a relationship with disaster preparedness school preparedness in the city of Denpasar, where low CIE can lead to a greater lack of preparedness for disaster preparedness school students after the variables of knowledge, attitude, facilities and infrastructure are controlled. Keywords: Preparedness Factors, Students, And Earthquake